Structural basis for broad neutralization of ebolaviruses by an antibody targeting the glycoprotein fusion loop - Benjamin M. Janus (Nature Portfolio, 2018)
The Ebola virus glycoprotein is a target for cross-protective antibodies. Here, Janus et al. report the crystal structure of the antigen-binding fragment of a pan-reactive antibody bound to a conserved epitope of the glycoprotein, facilitating rational design of cross-protective vaccines and therapeutics.